A review of the mygalomorph spiders of the Raveniola caudata species-group (Araneae, Nemesiidae) - Zonstein, Sergei (Zootaxa, 2009)
The caudata species-group of the genus Raveniola Zonstein 1987 is newly established and reviewed. The group includes R. redikorzevi (Spassky 1937) from Turkmenistan and R. caudata sp. n. from Tajikistan. Both members of the group differ from other congeners by the much longer posterior lateral spinnerets with long-digitiform apical segment, as well as by the characteristic, broadly-tipped and keeled embolus.